Pupils' Preconceptions about the Natural Phenomena at the Beginning of Primary Education - A Burden and/or an Opportunity - Sanja R. Blagdanić; Ivica V. Radovanović; Marija T. Bošnjak Stepanović (University of Belgrade, Teacher Education Faculty, 2019)
Learning about the world that surrounds a child begins well before the start of primary education. Experiential concepts, which children form in direct interaction with the environment, represent an experiential basis on which the formation of scientific concepts in the teaching process relies. Experiential notions based on ungrounded generalisations and misconceptions are also known as preconceptions, alternative ideas, and naive beliefs. The aim of this paper was to examine pupils' preconceptions about physical phenomena in the fields Physical Properties of Materials, Movement and Light at the beginning of primary education. The survey was conducted on a sample of 324 students, by using a criteria-based test of knowledge. The results of the research indicate that seven-year-olds from Serbia have some typical preconceptions and doubts that were confirmed by the previous research conducted in other countries (United Kingdom, USA). The respondents had the fewest misconceptions about the movement of bodies, while they mostly had wrong beliefs about the physical properties of materials. Given that the identification of the preconceptions that pupils have at the beginning of primary school can be useful for the creators of educational policies, textbook authors and teachers when deciding which physical phenomena should be given additional attention because they are not well understood by students, or what phenomena are pupils already familiar with, a more in-depth research of this content in teaching is necessary.